THE INFLUENCING FACTORS OF PERSONAL TAX COMPLIANCE ON REPORTING ANNUAL INCOME TAX RETURN - Emmy Indrayani; Euphrasia Suzy Suhendra (Universitas Gunadarma, 2018)
Taxpayer reporting compliance has been a classic problem in every nation. Therefore, the taxpayer's behavior needs to be well understood, so as to create a good synergy between the government and the public. A good cooperation between government and citizen on this matter will accelerate the development of the country. This study was conducted to determine the awareness level of taxpayers, perceived tax return filling process, perceived service quality, perceived form and assistance and perceived sanctions, and examined the effect of those variables on tax compliance on the delivery of Annual Income Tax Return. Questionnaires we used to collect data from the taxpayer as a respondent. Questionnaires filled by interview face to face to minimize the possibility of biased answers. The number of respondents was 60 Indonesia citizens in West Java Province, active taxpayers, employed and have a regular income taxable. Data analysis was using partial least square. The study period is in the month of March 2016. The results show that tax compliance affected by awareness level of taxpayers, perceived service quality and perceived comfort of facilities. As for the perceived tax return filling process and sanctions does not significantly influence taxpayer compliance on reporting annual income tax return. Keywords: taxpayer, annual income tax return, compliance, behavior, perceived service